Five new species of freshwater crabs (Crustacea: Decapoda: Brachyura: Potamidae) from China - Naruse, Tohru; Yeo, Darren C. J.; Zhou, Xianmin (Zootaxa, 2008)
Two species of Latopotamon Dai & Türkay, 1997, one species of Trichopotamon Dai & Chen, 1985, all from Yunnan Province, China, and two species of Sinopotamon Bott, 1967, from Hu’nan Province, China, are described as new. The new species are compared with the most similar congeners. This study brings the number of species of Latopotamon to three, Sinopotamon to 81, and Trichopotamon to two.